2012
DOI: 10.1080/09540121.2012.712671
|View full text |Cite
|
Sign up to set email alerts
|

Intimate relationships in young adults with perinatally acquired HIV: Partner considerations

Abstract: Due to developments in anti-retroviral treatment, an increasing number of children with perinatally acquired HIV are now surviving into late adolescence and young adulthood. This cohort is facing normative challenges in terms of their intimate relationships as well as challenges that face all individuals with HIV regardless of the route of transmission (for example, concerns about disclosure). There may be additional issues specific to having grown up with HIV that affect intimate relationships, for example, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…5 Further, HIV disclosure is one of the most challenging components of engaging in romantic relationships and is fraught with anxiety. 22,23 There is evidence to support the efficacy of disclosure-oriented counseling from providers in increasing the likelihood of disclosure in romantic relationships among adults with HIV as well as the disclosure to children. 24,25 Most providers (73.1%) reported pregnancies among female patients with PHIV at their clinics (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…5 Further, HIV disclosure is one of the most challenging components of engaging in romantic relationships and is fraught with anxiety. 22,23 There is evidence to support the efficacy of disclosure-oriented counseling from providers in increasing the likelihood of disclosure in romantic relationships among adults with HIV as well as the disclosure to children. 24,25 Most providers (73.1%) reported pregnancies among female patients with PHIV at their clinics (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have found that disclosing HIV status to a sexual partner often results in negative outcomes such as rejection by romantic partners and/or the community and stigma [30], [ 31]. Previous rejection, fear of rejection, and thinking about partner perceptions have often been reported as barriers for disclosing HIV status to the sexual partner [31], [ 32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous rejection, fear of rejection, and thinking about partner perceptions have often been reported as barriers for disclosing HIV status to the sexual partner [31], [ 32]. WHO recognizes disclosure as a complicated issue and recommends that “adolescents be counseled about the potential benefits and risks of disclosure of their HIV status and empowered and supported to determine if, when, how and to whom to disclose” [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, health beliefs and attitudes are also much more likely to be culturally specific which has potential impacts on the active role of children in decision-making and inclusion (Seery, 2010). Greenhalgh et al (2013) intimated a possible association between the ethnic background of parents and the frame of reference used to perceive the condition within families and this is of particular relevance due to the proportion of children affected by HIV in the UK coming from a Black African ethnic background.…”
Section: Experience Of Disclosurementioning
confidence: 99%
“…Advances in HIV treatment including accessibility to antiretroviral therapies have meant that for many of these children and young people, they are living beyond original expectations and leading much healthier lives (Wiener and Battles, 2006;Greenhalgh et al, 2013;Fair et al, 2016). Mortality and morbidity rates have improved significantly, and for many the perception of living with HIV has transformed from being viewed as an acute terminal illness to a chronic condition and consequently these young people now confront living with HIV as such and the challenges that go with living with chronic conditions (Sopen et al 2010, Hogwood et al 2012.…”
Section: Introductionmentioning
confidence: 99%